PP103 A Comparative Study Of Catastrophic Health Expenditure In China. (2019) - Zhen, Xuemei; Zhang, Hao; Hu, Xiaoqian; Gu, Shuyan; Li, Yuanyuan; Gu, Yuxuan; Huang, Minzhuo; Sun, Xueshan; Wei, Jingming; Dong, Hengjin
Abstract : Introduction: China has made great achievements in health insurance coverage and healthcare financing. Nonetheless, the rate of catastrophic health expenditure (CHE) in China was 13 percent in 2008, which is higher than in some other countries. There are differences among the provinces in China in terms of the lifestyles, customs, prevalent medical conditions, and health consciousness of their populations. This study aimed to compare the proportion of households with CHE and the factors influencing this expenditure between the Zhejiang and Qinghai province in China. Methods: Data were derived from household surveys conducted in Zhejiang and Qinghai. Sampling was based on a multi-stage, stratified random cluster method. Households with CHE were defined as those with an out-of-pocket payment for health care that was at least 40 percent of the household income. Univariate and multivariate logistic regression analyses were used to identify the factors associated with CHE. Results: A total of 1, 598 households were included: 995 in Zhejiang and 603 in Qinghai. The average rates of CHE in Zhejiang and Qinghai were 10 percent and 31 percent, respectively. The economic status of a household influenced the likelihood of experiencing CHE; households headed by an employed person were less likely to experience CHE. In contrast, households that included outpatients or individuals with chronic diseases had a higher risk of experiencing CHE across the two provinces. Poorer or uninsured households in Zhejiang were more likely to experience CHE, as were households in Qinghai that included outpatients or were headed by a person from a minority nationality. Conclusions: This study highlighted the importance of promoting economic development, expanding employment, and adjusting policies to better protect individuals with chronic diseases and outpatients from the risk of CHE. The Chinese government should pay more attention to actual conditions in different provinces to ensure that policy decisions incorporate local knowledge.